PSIX-15 A pilot study to investigate the relationship between social behavior and serum metabolite concentration in finisher pigs. (7th December 2018) - Dervishi, E; van der Zande, L; Reimert, I; Mathur, P; Knol, E; Plastow, G
Abstract: Social behaviour of group housed pigs is important for their welfare, health and productivity. A new breeding method including Indirect Genetic Effects, to reduce aggression in pigs was proposed. The purpose of this study was to identify important metabolites related to pig behavior and whether there are alterations in serum metabolites in animals selected for positive or negative estimated IGE for growth. Animals involved in the present study were part of a much larger study carried out at Wageningen University and Research. Here we used 48 Tempo x Topigs-20 finisher animals divided over 2 batches balanced regarding gender, selected for positive IGE for growth (27 animals) or negative IGE (21 animals). Blood samples collected at 22 weeks of age were used to determine metabolic profiles using Nuclear Magnetic Resonance (NMR), with the Absolute-IDQ platform kit (Biocrates AbsoluteIDQTM p180 Kit, Biocrates Life Science AG, Innsbruck, Austria). Finally, a catecholamine assay was performed to quantify dopamine, epinephrine, tyramine, metanephrine, normetanephrine and phenylethylamine. Univariate statistical analyses were performed using R by fitting a Linear Mixed Model. Statistical significance was declared when P<0.05. Positive IGE animals had lower concentration of serotonin (5.79 ± 0.70 vs 7.64 ± 0.51 µM), epinephrine (0.54 ± 0.40 vs 2.52 ± 0.29 µM), aspartate and greater concentration of serum phenylethylamine, glycerol, pyruvic acid, creatinine, malonate, acetone, propylene glycol and dimethyl sulfone when compared to negative IGE (all, P<0.05). Positive IGE animals had a lower ratio of tryptophan/kynurenine (P<0.05). Tryptophan is the precursor of serotonin which affects behavior in humans and animals. Lower concentration of epinephrine and higher concentration of phenylethylamine might suggest that Sympathetic-Adrenal-Medullary (SAM) axis response is lower in positive IGE animals. In conclusion, selection for IGE for growth is associated with changes in the concentration of several metabolites in the serum of finisher pigs. These metabolites are being tested on a larger number of samples.